A conditional embrace—Swedish LGBTQ+ spaces through the eyes of ethnic minority non-heterosexual individuals - Miller, Emelie Louise (Frontiers in Psychology, 2022)
Introduction In research on sexuality, marginalized sub-groups within sexual minorities have often been overlooked. From the vantage point of Sweden, internationally ranked as an exemplary progressive nation in equality issues and LGBTQ+ rights, and with an increasingly diversified population, the lived experiences of ethnic minority non-heterosexual people are still very much lacking in voice and visibility. The present study aimed to examine experiences within Swedish non-heterosexual spaces, held by ethnic minority non-heterosexual individuals. Method A thematic analysis of in-depth interviews with 22 Swedish non-heterosexual individuals, 13 cis-men and nine cis-women, with diverse first- and second-generation immigration backgrounds, was conducted. Results Two main themes were identified. The first theme, “Constantly contested identities,” is composed of the sub-themes “Ingrained, intersecting ideals” and “Prejudiced spaces,” and the second theme, “Effects and counteractions,” of the sub-themes “Never fully human” and “Representation and separatism.” The results, presented starting from a more theoretical level, moving to situated knowledge, and finally to psychological and practical implications, demonstrate that ethnic minority non-heterosexual people experience problematic and intersecting ideals, with related discrimination, in various Swedish non-heterosexual settings. Experiences of alienation, exotification, and tokenism were common among the participants and had negative psychological effects, including multiple-minority stress and a constant outsider feeling. Representation and participation in separatist forums were utilized as primary strategies to counteract the negative effects. Discussion The findings shed light on previously under-researched ideals and actions within Swedish LGBTQ+ spaces, and raises questions about how positive belonging can be achieved for multiple-minorities. Further research and continued critical discussions about ethnic minority non-heterosexual people's plight within non-heterosexual settings in Sweden, and beyond, is advocated.